KAJIAN METODE PELAKSANAAN SISTEM POLDER KALI BANGER - dwi Subandriyani; Muchammad Lutfian Nabil; Suharyanto Suharyanto; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Banger river polder system which has 524 ha area is a part of Semarang Centre region drainage system. Banger river polder system is located in East Semarang region and North Semarang region. It is a crowded area with many problems. This area which has low level at soil supporting capacity is flooded by rob almost everytime. So it causes land subsidence every year. On the other hand, land use is another serious problem there with many houses cover the area without proper access road. Construction method evaluation of procurement and pump installation and retention pond and closer dike construction in Banger river polder system need to adapt more further with the real condition on site. Procurement and pump installation works will not be affected significantly by Banger river polder system site location. So that, in retension pond and closer dike works need a construction method which uses dewatering work, temporary dike construction, and determining the hauling route. These works combination produce an effective construction method, construction method using dewatering and bailey bridge. This construction method is a combination between dewatering work and the use of bailey bridge which is based on workability, reducing cycle time, and the economical one. This combination is the most effective, based on work influence indicators which reach 27,05%